Ontology, Epistemology, and Axiology of Islamic Educational Philosophy: An Introduction - Ni'mah, Siti Jaroyatun; Murjazin, Murjazin; Nurhuda, Abid; Lathif, Nur Muhammad; Al Fajri, Muhammad (Matan : Journal of Islam and Muslim Society, 2024)
Education is necessary in a society where the development of the times challenges changes in human behavior. So, we need new formulations that are comprehensive regarding the concept of education, especially Islamic education, which is studied in the field of philosophy. The purpose of this study is to describe the ontology, epistemology, and axiology of Islamic education philosophy. The method used is qualitative with literature study techniques when collecting data, then analyzed descriptively and finally concluded to answer the problem. The research results show that ontology includes foundation, criticism, correction, and evaluation. While Epistemology includes sources, approaches, methods, and objects. The axiology in Islamic education philosophy includes the values of worship, ihsan, future, mercy, trust, da'wah, and tabsyir.